A prática de gestão de vendedoras de cosméticos em uma organização multinacional - uma análise situada da dimensão ideológica da emoção - Jost, Rossana Cristine Floriano (2016)
This work aims to reveal the ideological dimension of the emotion in the management practice of informal cosmetics sellers from a situated analysis which was developed based in a North American multinational company and placed in Curitiba-PR. This research refers to the practice studies and it is supported by the theory of Social-Historical and Cultural Psychology; such approaches are based in a human vision as a concrete, conscious, social, historical and cultural being. Thus, the concept of emotion for this study is faraway itself from funcionalist-positivist approach, by their rationalist texts, hitherto dominant into organizational studies. Emotion is embedded as a valued social situation and inserted in the individual experience of the activity, acquiring meaning and sense. The theoretical and methodological context is a qualitative study that uses autoethnografy as the main option, a knowledge production mode which is based in affective and cognitive experiences of researcher. Therefore, the researcher was inserted into empirical field, assuming genuine activities, tasks and responsibilities of a informal cosmetics sellers from the company. Furthermore, the study considers the experiences of some sellers, through in-depth interviews, participant observation and documental analysis, all analyzed according to the analysis technique of discourse signification core. The results show emotion as construction of meaning into activity, filled with ideological content and linked with female imaginary from the culture that permeates the organization, in which these women saleswomen constituted themselves. Even the activity is interrupted, it continues to act on them, interfering in their personal lives, mobilizing them subjectively. The emotional appeal of the company's management are attached to their models and expectations, present into the established ideological universe, establishing the lenses through which their view of the world is constituted.